2018
DOI: 10.1038/s41598-018-25561-y
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity Analysis According to Sex and Age towards Cardiovascular Diseases of Adults in Northeast China

Abstract: Non-communicable diseases (NCDs) are great challenges in public health, where cardiovascular diseases (CVD) accounted for the large part of mortality that caused by NCDs. Multimorbidity is very common in NCDs especially in CVD, thus multimorbidity could make NCDs worse and bring heavy economic burden. This study aimed to explore the multimorbidity among adults, especially the important role of CVD that played in the entire multimorbidity networks. A total of 21435 participants aged 18–79 years old were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
4
18
0
Order By: Relevance
“…Our results are similar to the ones obtained for older adults from Northeast China, where the pair combination of hypertension and cardiovascular diseases was the second most prevalent among older adults [26]. In women, the most prevalent individual diseases were (from highest to lowest) hypertension, musculoskeletal disorders, and diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are similar to the ones obtained for older adults from Northeast China, where the pair combination of hypertension and cardiovascular diseases was the second most prevalent among older adults [26]. In women, the most prevalent individual diseases were (from highest to lowest) hypertension, musculoskeletal disorders, and diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…[38] Studies have also suggested a slightly higher morbidity in older females compared with males in some populations, [62,63] with a study from China suggesting that older females have more comorbidities than males. [64] Since morbidity is a determinant of increased SIV uptake, as reported in this review (as well as other studies), the observed variation in the association of sex with SIV uptake in Asia compared with Europe could be a result of more morbidity among older females compared with males in the studies from Asia.…”
Section: Plos Onesupporting
confidence: 58%
“…The average degree was defined as the average of the degrees of all nodes. The larger the network density (or average degree), the denser the network [20,21]. All statistical analyses were performed with R version 3.6.1 (University of Auckland, Oakland, New Zealand).…”
Section: Statistical Analysesmentioning
confidence: 99%